PP-47 Off-label use of tacrolimus in children with henoch-schonlein purpura nephritis: efficacy and safety. Issue 10 (20th September 2017) - Zhao,; Zhang,; Hao,; Li,; Dong,; Dong,; Jacqz-Aigrain,; Shi,
Abstract : Background: Tacrolimus was used off-label in the treat-ment of Henoch-Schönlein purpura nephritis (HSPN) in children. The objective of this pilot study was to assess its efficacy and safety. Methods: Children with HSPN receiving tacrolimus and steroids as empirical treatment was included. Urine protein was assessed every 2 weeks during treatment. Pharmacogenetic analysis was performed on the CYP3A5 gene. Results: A total of 25 patients with a mean age of 7.2 (range 3–12) years was included in this study. Pro-teinuria returned to negative in 21 patients with a mean treatment duration of 101 (SD 75) days. Patients with CYP3A5*1/*3 had longer duration of treatment achiev-ing negative proteinuria as compared with patients with CYP3A5*3/*3 (131±97 versus 80±39 days). No patients discontinued the tacrolimus treatment due to adverse events, and no drug-related adverse events were shown to have a causal association with tacrolimus therapy. Conclusion: This preliminary study shows that tacrolim-us might be an effective, and well-tolerated drug for the treatment of HSPN in children.